Costs of Information in Skills Training Programs in Smes: A Field Experiment in Publicity Services - Moloche, Guillermo (2016)
Workers and micro SMEs often lack time and attentional resources to acquire the technical and business skills necessary to increase productivity. Provide training for digital media is a possible solution to this problem as it adapts to the availability of time workers and employers and allows interactively customize the content so that learning is maximized. To test this hypothesis, we conducted an experimental evaluation using a randomized controlled trial in a Peruvian company advertising services to verify that, providing training intervention based on technologies of e -learning of second generation that is suited to the capabilities care and busy work schedule of employees of SMEs, the understanding of the content of training and labor productivity is increased.